2011
DOI: 10.1021/jm100972f
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Soft Val-boroPro: A Strategy for Enhancing in Vivo Performance of Boronic Acid Inhibitors of Serine Proteases

Abstract: Val-boroPro, 1, is a potent, but relatively nonspecific inhibitor of the prolyl peptidases. It has antihyperglycemic activity from inhibition of DPPIV but also striking anticancer activity and a toxicity for which the mechanisms are unknown. 1 cyclizes at physiological pH, which attenuates its inhibitory potency >100-fold, which is a "soft drug" effect. Here we show that this phenomenon can be exploited to create prodrugs with unique properties and potential for selective in vivo targeting. Enzyme-mediated rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The prosoft compound cyclohexyl(glycine)-Pro-Val-boroPro (Chg-Pro-Val-boroPro) was used to show proof of principle (Poplawski et al, 2011). This approach can preserve the inhibitory activity of the compound, so that it is only activated and reactive with the target protease.…”
Section: Fap Release Of Prodrugsmentioning
confidence: 99%
“…The prosoft compound cyclohexyl(glycine)-Pro-Val-boroPro (Chg-Pro-Val-boroPro) was used to show proof of principle (Poplawski et al, 2011). This approach can preserve the inhibitory activity of the compound, so that it is only activated and reactive with the target protease.…”
Section: Fap Release Of Prodrugsmentioning
confidence: 99%
“…show proof of principle (Poplawski et al, 2011). Chg-Pro-Val-boroPro is specifically cleaved and activated by DPPIV, after which it exhibits long-lasting DPPIV inhibition with reduced toxicity in rats, as compared to Val-boroPro (Poplawski et al, 2011).…”
Section: Fap Release Of Prodrugsmentioning
confidence: 90%
“…show proof of principle (Poplawski et al, 2011). Chg-Pro-Val-boroPro is specifically cleaved and activated by DPPIV, after which it exhibits long-lasting DPPIV inhibition with reduced toxicity in rats, as compared to Val-boroPro (Poplawski et al, 2011). This strategy could be exploited to design a target portion of pro-soft Val-boroPro, Gly-boroPro or other dipeptide boronic acid derivative that makes it specific to FAP.…”
Section: Fap Release Of Prodrugsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the known coordination of neighboring amides and amines to boronic acid moieties, we were interested in seeing if similar interactions in peptide boronic acids were at work . Upon analysis of our generated compounds, we found that there was no interaction between the adjacent carbonyl amide oxygen and the tethered boronic acid moiety at various pHs.…”
Section: Introductionmentioning
confidence: 99%